Work Stress, Health Status and Presenteeism in Relation to Task Performance Among Chinese Medical Staff During COVID-19 Pandemic - Huanhuan Jia; Panpan Shang; Shang Gao; Peng Cao; Jianxing Yu; Xihe Yu (Frontiers Media S.A., 2022)
ObjectivesThis study aims to evaluate the direct effects of work stress, health status and presenteeism on task performance, and further explore the mediating effects of health status and presenteeism, hoping to provide theoretical basis for improving the performance of medical staff.MethodsA cross-sectional study was conducted among medical staff in Jilin Province, Northeast China. The Challenge and Hindrance-Related Self-Reported Stress scale, Short Form-8 Health Survey scale, Stanford Presenteeism Scale and Task Performance Scale were adopted to assess the work stress, health status, presenteeism and task performance of medical staff.ResultsA total of 4,347 questionnaires were distributed among medical staff, and 4261 were valid, for an effective rate of 98.02%. The mean scores for work stress, health status, presenteeism and task performance were 2.05 ± 0.84, 4.18 ± 0.68, 2.15 ± 0.79 and 4.49 ± 0.64, respectively. The ANOVA results showed that there were significant differences in the task performance scores between different genders, ages, marital statuses, professional titles, departments and work years (P < 0.05). Work stress (β = −0.136, P < 0.001) and presenteeism (β = −0.171, P < 0.001) were negative predictors of task performance. Health status (β = 0.10; P < 0.001) was positive predictor of task performance. Health status (β = −0.070; P < −0.001) and presenteeism (β = −0.064; P < 0.001) mediated the relationship between work stress and task performance (P < 0.001). Presenteeism mediated the relationship between health status and task performance (β = 0.07; P < 0.001).ConclusionWork stress and presenteeism had significant negative impact on the task performance of medical staff; health status had a significant positive effect on task performance. Meanwhile, health status and presenteeism played a mediating role in the relationship between work stress and task performance, and presenteeism played a mediating role in the relationship between health status and task performance. Reasonable assignment of tasks can reduce the work stress, but to improve the performance of medical staff, we should pay more attention on improving health, such as making health-related safeguard measures, raising awareness, building a platform, etc.